Kondisi Manajemen Pengetahuan Perguruan Tinggi Swasta di DKI Jakarta - Dyah Budiastuti (Bina Nusantara University, 2013)
Globalization affects not only economic sector, but also education sector especially higher education. It changes the mindset on managing university as higher education executant which is responsible in producing science and technology. As an organization focusing on human capital, a university should have ability in knowledge management. This research aims to determine the conditions of knowledge management on privateuniversities in Jakarta, and to propose the implementations of knowledge management which could create value. The study was conducted on 184 private universities in Jakarta with descriptive statistical analysis methods. The results showed that the conditions of knowledge management on the universities have not been able to create value for the universities concerned. So that, the implementations should be linked to the provision of knowledge management components, such as the provision of information technology, the process management, and theprovision/improvization on human capital capability in managing knowledge management systems.